(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article deals with lexical meaning and semantic branching of names of wild trees, in particular oak and chestnut, which are represented in the Ukrainian poetic texts of the late twentieth. There are determined the characteristic of the symbolical features, archetypal origin and functional activity of the analyzed nomenaes, proved their relationship with the traditions and beliefs of the Ukrainian people.